An explicit hybrid-stabilised eighteen-node solid element for thin shell analysis - Tay, Ming Hui. (2009)
In this dissertation, the explicit hybrid stabilisation method is applied to formulate stabilisation vectors for the uniformly reduced integrated eighteen-node solid element. An assumed contravariant stress is devised based on the strain associated with the commutable mechanisms of a geometrically regular element. It will be seen that the stabilisation vectors can be derived and programmed explicitly without resorting to numerical integration loops. Admissible matrix formulation is employed in evaluating the flexibility matrix which becomes diagonal and thus induces no inversion cost. The element accuracy is comparable to other state-of-the-art nine-node shell and eighteennode solid elements. FORTRAN subroutines to constructing the stabilisation vectors are also presented.